Process Parameter Optimization for Minimizing Vibrations and Surface Roughness During Turning EN19 Steel Using Coated Carbide Tool. (2020) - Shankar, N.V.S.; Ravi Shankar, H.; Pavan Kumar, N.; Saichandu, K.
Abstract: In modern manufacturing environments, the quality assurance of machined parts has attracted great attention from manufacturers. Surface finish and vibrations during turning play an important role during this process. Comparatively less work is done in the field of process parameter optimization. EN19 is a hard steel which finds its application in shafts, gears, spindles, oil and gas industries. Due to the hardness of the material, 223-277 BHN, turning this material is a difficult task. Thus, optimization of various cutting parameters is required in this situation. In the current work, an attempt has been made to optimize machining parameters when turning EN19 with coated carbide inserts (Titanium Nitride coated CCMT060204-HM YBC251 inserts) on conventional lathe machine. During this process, three factors, namely, MQL Condition (2 levels), Depth of cut (3 levels) and Spindle Speed (3 levels) are considered. Mixed level optimization is performed using Taguchi analysis with L18 orthogonal array. The considered factors/parameters are optimized for Surface Roughness and Vibrations with the objective functions being to minimize the same